2011
DOI: 10.1038/hr.2010.264
|View full text |Cite
|
Sign up to set email alerts
|

The role of oxidative stress in the pathophysiology of hypertension

Abstract: Hypertension is considered to be the most important risk factor in the development of cardiovascular disease. An increasing body of evidence suggests that oxidative stress, which results in an excessive generation of reactive oxygen species (ROS), has a key role in the pathogenesis of hypertension. The modulation of the vasomotor system involves ROS as mediators of vasoconstriction induced by angiotensin II, endothelin-1 and urotensin-II, among others. The bioavailability of nitric oxide (NO), which is a major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
275
2
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 354 publications
(289 citation statements)
references
References 159 publications
(182 reference statements)
5
275
2
7
Order By: Relevance
“…Numerous studies have reported that systemic oxidative stress is elevated in chronic disease conditions including heart failure, hypertension, and Type 2 diabetes mellitus (9,19,33,37,38). Likewise, NADPH oxidase activity has been reported to be increased in disease states, particularly hypertension (5,15).…”
Section: Perspectives and Significancementioning
confidence: 99%
“…Numerous studies have reported that systemic oxidative stress is elevated in chronic disease conditions including heart failure, hypertension, and Type 2 diabetes mellitus (9,19,33,37,38). Likewise, NADPH oxidase activity has been reported to be increased in disease states, particularly hypertension (5,15).…”
Section: Perspectives and Significancementioning
confidence: 99%
“…On the other hand some drugs such as angiotensin inhibitors or angiotensin blockers also may adversely affect renal perfusion and GFR in the elderly individuals. Excessive oxidative stress, an imbalance between reactive oxygen species (ROS), and nitric oxide (NO), due to xanthine oxidase activity and vascular dysfunction have been reported in hypertension, diabetes, and atherosclerosis (2). Dysfunction of endothelial cells caused by ROS implicated in the pathogenesis of vascular diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Important contributors to these changes are endothelial dysfunction and vascular oxidative stress (1). Hypertension accelerates this age-related vascular dysfunction, and thus has an impact on progression of vascular damage and decreases GFR in an elderly population (2). On the other hand some drugs such as angiotensin inhibitors or angiotensin blockers also may adversely affect renal perfusion and GFR in the elderly individuals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For centuries, the pathogenesis and maintenance of blood pressure in hypertension was attributed by oxidative stress [1,2]. Oxidative stress served as an important mediator between vasoconstrictor and vasodilator mechanisms in both experimental and human [2][3][4].…”
mentioning
confidence: 99%